Long-term NO2 exposures and cause-specific mortality in American older adults - Ki-Do Eum; Fatemeh Kazemiparkouhi; Bingyu Wang; Justin Manjourides; Vivian Pun; Virgil Pavlu; Helen Suh (Environment International, 2019)
Background: The impact of long-term exposure to nitrogen dioxide (NO2) on cause-specific mortality is poorly understood. Objective: To assess mortality risks associated with long-term NO2 exposure and evaluate confounding of this association. Methods: We examined the association between 12-month moving average NO2 exposure and cause-specific mortality in 14.1 million US Medicare beneficiaries between 2000 and 2008. Associations were examined using age, gender, and race-stratified and state-adjusted Poisson regression models. We assessed the potential for confounding by PM2.5 and behavioral covariates and unmeasured confounding by decomposing NO2 into its spatial and spatio-temporal components. Results: We found significant associations between 12-month NO2 exposure and increased mortality from all-causes [risk ratio (RR): 1.052; 95% CI: 1.051, 1.054; per 10 ppb], cardiovascular (CVD) (1.133; 95% CI: 1.130, 1.137) and respiratory disease (1.050; 95% CI: 1.044, 1.056), all cancers (1.021; 95% CI: 1.017, 1.025), ischemic heart disease (IHD) (1.221; 95% CI: 1.217, 1.226), cerebrovascular (CBV) disease (1.092; 95% CI: 1.085, 1.100), and for the first time pneumonia (1.275; 95% CI: 1.263, 1.287). Associations generally remained positive and statistically significant after adjustment for PM2.5 and behavioral factors. Conclusions: Our findings provide additional evidence of the increased risk posed by long-term NO2 exposures on increased mortality from all-causes, CVD, respiratory disease, IHD, CBV, and cancer and provide new evidence of their impact on mortality from pneumonia. Unmeasured confounding of these associations was present, however, demonstrating the need to understand sources of this confounding.